KAJIAN PENURUNAN EMISI GAS RUMAH KACA SEKTOR KEHUTANAN UNTUK MENDUKUNG KEBIJAKAN PERPRES NO. 61/2011 - Ari Wibowo (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2013)
Presidential Regulation No. 61 on the National Action Plan for Green house Gas (GHG) Emission Reduction, has been issued and used as general guidance for emission reduction. However, this regulation requires support of more detail technical information as a direction in the implementation of emission reduction activities in forestry sector. In the field, the implementation of emission reduction should be based on activities that directly and indirectly generate emission reductions. This study aims to support emission reduction activities through the understanding of emission sources in Indonesia and identify activities that directly can be quantifi edits emission reduction through carbon conservation activities as well as the increase of source of carbon enhancement through growth of forests and planting activities such as timber estates, community forest plantation, land rehabilitation movement and other planting activities. Forestry activities related to climate change mitigation to reduce GHG emissions, in principle, can be grouped into three main categories, namely, conservation of forest carbon, increase carbon stock through af forestation, reforestation and other management practices, and use of biomass as a replacement for fossil fuels. Potential emission reduction from deforestation is still quite large with an average deforestation rate of 1.1 million haper year in 2000-2005 and 0.83 million haper year in 2006-2009. Reducing emissions from deforestation can be seen from the potential of natural forests in Indonesia that couldreach of 600 tonnes Carbon/Ha. While the potential of planting can be seen from the plantation stocks that reached 177 tonnes Carbon/Ha. Results of this review showed that activities in appendix of presidential regulation No 61/2011 were dominated by supporting activities. This review also provided information on activities that directly can reduce emission as inputs for preparation of regional action plans (RAD) of emission reduction.